The Implications of Multiple Repeat Cesarean Deliveries on Maternal Morbidity - Can, Esra; Oğlak, Süleyman Cemil (Gynecology Obstetrics & Reproductive Medicine, 2023)
OBJECTIVE: This study aimed to assess the obstetric outcomes of cesarean delivery (CD) in a cohort of pregnant women who had a history of four or more previous CDs and compared them with those who had a history of three or fewer previous CDs. STUDY DESIGN: The cohort of this retrospective study consisted of all pregnant women who gave birth in our hospital via elective or emergency CD and who had previously undergone one or more other cesarean sections. Pregnant women who had a history of four or more CDs were included in the multiple repeat CD group, and cases who had a history of fewer than 4 CDs were enrolled in the lower-order repeat CD (comparison) group. Demographic data, medical history, clinical features, intraoperative events, and postoperative complications were recorded. RESULTS: The multiple repeat CD group comprised 63 women, and the lower-order repeat CD group (comparison group) included 1097 cases. Intraabdominal dense adhesions (28.6% versus 14.1%, p=0.002), placenta previa (11.1% versus 4.1%, p=0.009), placenta accreta spectrum (PAS) (7.9% versus 2.4%, p=0.008), bladder injury (6.3% versus 1.7%, p=0.011), intraoperative massive hemorrhage (7.9% versus 2.2%, p=0.004), uterine artery ligation (4.8% versus 1.1%, p=0.012), internal iliac artery ligation (4.8% versus 1.2%, p=0.008), cesarean hysterectomy (4.8% versus 1.5%, p=0.045), blood transfusion (12.7% versus 4.1%, p=0.001), and maternal intensive care unit (ICU) admission (14.3% versus 2.0%, p<0.001) were significantly more common among women in the multiple-repeat CD group compared with the lower-order repeat CD group. CONCLUSIONS: Pregnant women having multiple repeat CDs have a significantly increased risk of dense adhesions, placenta previa, PAS, intraoperative massive hemorrhage, blood transfusion, bladder injury, additional surgical interventions, including uterine artery ligation, internal iliac artery ligation, cesarean hysterectomy, and maternal ICU admission.